2018
DOI: 10.1177/0894318418774947
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Nursing Theory: Infant Sleep and Development

Abstract: Although well positioned to work with families of young children, nurses do not yet have a theory that guides practice and research by relating infant sleep to child and family development. The authors of this paper describe a proposed theory that combines Bronfenbrenner's bioecological theory of human development with the Barnard model of parent-child interaction to inform nursing practice and research related to infant sleep and optimizing child and family development. The theory focuses on sustainability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 41 publications
0
13
0
3
Order By: Relevance
“…Chart 1 shows the selected studies according to country, year, databases, and title. Of the 21 publications, nine studies (42%) were conducted in the United States (13)(14)(15)(16)(17)(18)(19)(20)(21) , four (19%) in Brazil (22)(23)(24)(25) , two (9%) in Canada (26,27) . Countries such as Mexico (28) , Iran (29) , Portugal (30) , Finland (31) , Sweden (32) , and the United Kingdom (33) presented only one (5%) study each.…”
Section: Resultsmentioning
confidence: 99%
“…Chart 1 shows the selected studies according to country, year, databases, and title. Of the 21 publications, nine studies (42%) were conducted in the United States (13)(14)(15)(16)(17)(18)(19)(20)(21) , four (19%) in Brazil (22)(23)(24)(25) , two (9%) in Canada (26,27) . Countries such as Mexico (28) , Iran (29) , Portugal (30) , Finland (31) , Sweden (32) , and the United Kingdom (33) presented only one (5%) study each.…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare workers prioritise ward routines above sleep to the extent that child healthcare staff have poor insight into the sleep disruptions associated with the care they provide (Peirce et al 2018 ). Theoretical frameworks were identified that guide nurses to promote sleep in the context of infant development (Keys & Benzies 2018 ), but no age-appropriate guideline was identified. Relying on adult literature from high income settings required modification of recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…In-hospital, familial involvement maximises limited resources, decreases staff burnout and improves patient safety (Micalizzi et al 2015 ). Families desire to be involved in their child’s hospital care (Bisogni et al 2015 ; Micalizzi et al 2015 ; North et al 2020 ) and the intentional involvement of mothers and caregivers holds promise to promote sleep in hospitals by capitalising on nurse’s relational strengths (Keys & Benzies 2018 ). For the child and family, the benefits may extend beyond hospital discharge (Erondu et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations